614 Implantable cardiac monitors predict arrhythmic events in post-infarction patients with mildly reduced left ventricular ejection fraction. (8th December 2021) - Riverso, Vincenzo; Curcio, Antonio; Tempestini, Alessia; De Luca, Emilia; La Bella, Sabrina; De Luca, Simona; Critelli, Alessandra; Pasceri, Eugenia; Santarpia, Giuseppe; Indolfi, Ciro
Abstract: Aims: Complications of acute myocardial infarction (MI) can be life-threatening leading to sudden cardiac death. While guidelines recommend prompt revascularization and prolonged intensive care hospitalization, predictors of major adverse cardiovascular outcomes are yet poorly understood. The role of implantable cardioverter-defibrillators, even in cases of non-sustained arrhythmias is still debated. To date, it is unknown how to follow-up patients with mild cardiac dysfunction after MI. Implantable cardiac monitors (ICMs) can be helpful for stratifying patients in the early discharge period, and remote monitoring might speed up arrhythmia recognition and treatment. We investigated the role of remote monitoring of ICMs to detect arrhythmic events in post-MI patients without overt cardiac dysfunction. Methods and results: We enrolled 13 patients (9 males; 69.8 years) after either ST-segment ( N  = 7) or non-ST-segment elevation ( N  = 6) MI with a left ventricular ejection fraction (LVEF) >35%, admitted to our coronary care unit for urgent revascularization between September 2019 and September 2021. Twelve patients underwent percutaneous myocardial revascularization, whereas one was treated with medical therapy only. All patients received an ICM during hospitalization according to echo and EKG parameters. We considered LVEF ≤ 40% as sole risk factor or LVEF between 40% and 50% in addition to either PQ length prolongation, or QRS widening, or pathologic heart rate variability, or non-sustained ventricular tachycardia/paroxysmal advanced second degree atrioventricular block. Patients with multiple revascularization procedures and several hospital admissions were excluded. Implanted ICM were frequently monitored both remotely and in-office when required. During follow-up, brady- and tachy-arrhythmias were recorded in four patients (30.8%). The remote monitoring of the ICM documented new-onset atrial fibrillation, high-degree atrioventricular block, severe bradycardia, and sustained ventricular tachycardia. Three patients required hospitalization and upgrade of the implanted device with pacemakers and cardioverter/defibrillator. For arrhythmic risk stratification, patients were divided into two subgroups; group A included patients with LVEF 40% associated with heart rate > 60 b.p.m., PQ length >160 ms and QRS width >86 ms ( N  = 4); group B included patients with EF 41%/50%, PQ length <159 and QRS width <85 ms ( N  = 10). First group experienced more advanced rhythm disorders than group B ( P  < 0.05). Device implantation was significantly higher in group A ( P  < 0.05%). Conclusions: OFF-label implementation of ICMs coupled with remote device monitoring may be effective for early detection of serious adverse cardiac rhythm alterations in patients after MI and LVEF higher than 35%. Further monitoring is ongoing for assessing the occurrence of multiple arrhythmias or their increased occurrence.